2022
DOI: 10.1080/07853890.2022.2079149
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of opioid overdose in Baltimore, Maryland, 2012–2017: insights from emergency medical services

Abstract: Introduction An estimated 100,306 people died from an overdose from May 2020 to April 2021. Emergency Medical Services (EMS) are often the first responder to opioid overdose, and EMS encounter records can provide granular epidemiologic data on opioid overdose. This study describes the demographic, temporal, and geographic epidemiology of suspected opioid overdose in Baltimore City using data from Baltimore City Fire Department EMS encounters with the administration of the opioid antagonist naloxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Most attendances with naloxone administrations in our study were in homes and in high deprivation areas, and where the presenting complaint was unknown poisoning. With an even female/male split and a median age of 47 years, this patient cohort differed from younger and more male‐dominant cohorts described in Australia, 15 Norway, 19 Canada, 20 and the USA 18,21 . In our study, the proportion of patients who were administered naloxone and who were Māori was greater than their proportion of the general Aotearoa New Zealand population (23% vs .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Most attendances with naloxone administrations in our study were in homes and in high deprivation areas, and where the presenting complaint was unknown poisoning. With an even female/male split and a median age of 47 years, this patient cohort differed from younger and more male‐dominant cohorts described in Australia, 15 Norway, 19 Canada, 20 and the USA 18,21 . In our study, the proportion of patients who were administered naloxone and who were Māori was greater than their proportion of the general Aotearoa New Zealand population (23% vs .…”
Section: Discussioncontrasting
confidence: 60%
“…6 patients/day in their state of 8 million people 17 . City of Baltimore EMS in the United States of America (USA) administered naloxone at a rate of 1100 per 100 000 person‐years in 2017, 18 or 115‐fold compared to the 2017 rate in our study.…”
Section: Discussionmentioning
confidence: 56%
“…For example, results can feed into “bad batch alerts” systems. The SOAR (Safety, Outreach, Autonomy, Respect) Initiative in Ohio has developed a mobile application, modeled after a text messaging service in Baltimore [ 44 , 45 ], that alerts PWUD when overdoses have surged and when fentanyl has been detected and reported in multiple batches in a particular geographic area. Feeding results into a data stream that is trusted and used by PWUD maximizes the utility of data.…”
Section: Key Principlesmentioning
confidence: 99%
“…In the United States, various research reported opioid overuse and related accidents. [3][4][5] The rules on opioid disposal are different in across countries. The frequency of opioid related accidents may depend on the degree of strictness of the rules.…”
Section: Introductionmentioning
confidence: 99%